Cohort profile: The Western Australian Sleep Health Study - Mukherjee, S.; Hillman, D.; Lee, J.; Fedson, A.; Simpson, L.; Ward, Kim; Love, G.; Edwards, C.; Szegner, B.; Palmer, L. (2012)
Background: Epidemiologic and genetic studies of obstructive sleep apnoea (OSA) are limited by a lack of large-scale, well-characterized OSA cohorts. These studies require large sample size to provide adequate power to detect differences between groups. This study describes the development of such a cohort (The Western Australian Sleep Health Study) in OSA patients of Caucasian-European origin attending the only public sleep clinic in Western Australia (WA). Aims: The main aim of the study is to phenotype 4,000 OSA patients in order to define the genetics of OSA and its co-morbidities. Methods: Almost all underwent laboratory-based attended polysomnography (PSG). Results: Currently complete data (questionnaire, biochemistry, DNA, and PSG) has been obtained on over 3,000 individuals and will reach the target of 4,000 individuals by the end of 2010. In a separate but related study, we have developed a sleep study database containing data from all patients who have undergone PSG at the sleep laboratory since its inception in 1988 until the present day (over 30,000 PSG studies representing data from approximately 20,000 individuals). In addition, data from both cohorts have been linked prospectively to statutory health data collected by the WA Department of Health. Conclusion: This study will be the largest sleep clinic cohort database internationally with access to genetic and epidemiological data. It is unique among sleep clinic cohorts because of its size, the breadth of data collected and the ability to link prospectively to statutory health data. It will be a major tool to comprehensively assess genetic and epidemiologic factors determining OSA and its co-morbidities.